FREQUENCY AND PATTERN OF PSYCHIATRIC DISORDERS IN PATIENTS WITH VITILIGO - Ahmed, Ijaz; Ahmed, Sohail; Nasreen, Sarwat (Journal of Ayub Medical College Abbottabad, 2007)
Background: Vitiligo affects one to four percent of the population, regardless of age, race or sex. People with this disorder may experience emotional stress, particularly if vitiligo develops on visible areas of the body, such as face, hands, arms, feet, or on the genitals. Some feel embarrassed, ashamed, depressed, or worried about how others will react. Severel indices have been used from time to time to measure the extent of psychiatric disabilty caused by skin disorders. Regarding vitiligo, not much work has been done in Pakistan. This study was aimed to determine the frequency and pattern of psychiatric disorders amongst patients with vitiligo. Methods: This cross sectional study was conducted in the Departments of Psychiatry and Dermatology, Ziauddin University, KDLB campus, Karachi and Institute of Surgery and Medicine, Karachi from April 2004 to March 2006. Clinically diagnosed cases of vitiligo, belonging to both sexes, aged above 15 years, fulfilling the inclusion criteria were enrolled in the study. The study was conducted in 2 stages. In the first stage, psychiatric illness was detected with the help of GHQ 12 (Urdu version), a validated tool for screening general population. In the second stage, Psychiatric Assessment Schedule, Urdu version was administrated to every patient with high scores as per GHQ 12 to differentiate between the most frequent psychiatric disorders. All the findings were recorded, compiled and tabulated. Results: A total of 100 patients comprising 62 females and 38 males ranging between 15-60 years with a mean age of 24.6 years completed the study. Exposed parts of the body were involved in 64 patients while covered sites in 36. Of the patients studied, 54 were married and 46 unmarried. In accordance with the GHQ-12 screening, 42 patients were positive for psychiatric caseness comp rising 26 females and 16 males, 17 patients being married. Psychiatric caseness featured in patients below 30 years of age (28 patients) and those having exposed parts of the body being involved (27 patients). On evaluation with Psychiatric Assessment Schedule (PAS), major depressive illness (15), was the most frequent psychiatric illness followed by generalized anxiety (10), mixed anxiety and depression, social phobia, agarophobia and sexual dysfunction. Conclusion: Psychiatric caseness has a probable association with vitiligo, the frequency being influenced by variables of disease and life. Major depression and anxiety remain the most common psychiatric disorders in these patients. Keywords: Vitiligo, Psychiatric caseness, depression, Anxiety